Rekayasa Produk Tenun Sutra Berbasis Kebutuhan Dan Preferensi Konsumen Dalam Upaya Meningkatkan Daya Saing: Studi Kasus: Tenun Sutra Family - Andri Ikhwana; Muhamad Munna Ar Ridha (Institut Teknologi Garut, 2026)
This study aims to provide recommendations for the development of silk weaving products based on consumer needs and preferences in order to improve the competitiveness of Alam Family Silk Weaving in Garut Regency. This research was motivated by a significant decline in sales due to competition with synthetic textile products and lack of innovation in design and marketing. The Quality Function Deployment (QFD) method with the House of Quality (HoQ) approach was used to identify consumer needs and preferences through surveys and observations. The data obtained was then translated into technical specifications and product development strategies that are more in line with market expectations. The results of this study provide recommendations related to the development of motif design and material quality. It is hoped that these recommendations can help Tenun Sutra Alam Family improve competitiveness and maintain market share in the midst of global competition.